Pola Asuh Orang Tua Yang Bekerja Dalam Menumbuh Kembangkan Sosial Emosional Anak Usia Dini Di Kelurahan Mangasa Kecamatan Tamalate Kota Makassar - Nasrah Natsir; Rudi Amir; Herlina Herlina (Universitas Negeri Makassar, 2023)
The education of children in the family has a decisive role in achieving the quality of human resources. This is because through family education, individuals first learn and recognize the cultural value system in the form of special rules, norms, habits and examples from other communities. This study uses a qualitative approach and the focus of this research is parenting style, namely (1) authoritarian parenting and democratic parenting, (2) social emotional development of early childhood. The results of this study indicate (1) The authoritarian parenting pattern of parents towards children emphasizes that children can always obey the words and orders of their parents, so that children have limitations in doing the things they want. (2) Permissive parenting provides a lot of leeway for children to interact with anyone under any circumstances, thus children have the freedom to do whatever they want without clear and strict rules, (3) Democratic Parenting is a parenting pattern that prioritizes the interests of the child. child and control the child through control and supervision. Children are given the opportunity to express their opinions and act in accordance with the mutual agreement between parents and children.